Metagenome and Metatranscriptome Revealed a Highly Active and Intensive Sulfur Cycle in an Oil-Immersed Hydrothermal Chimney in Guaymas Basin - He, Ying; Feng, Xiaoyuan; Fang, Jing; Zhang, Yu; Xiao, Xiang (Frontiers in Microbiology, 2015)
The hydrothermal vent system is a typical chemosynthetic ecosystem in which microorganisms play essential roles in the geobiochemical cycling. Although it has been well-recognized that the inorganic sulfur compounds are abundant and actively converted through chemosynthetic pathways, the sulfur budget in a hydrothermal vent is poorly characterized due to the complexity of microbial sulfur cycling resulting from the numerous parties involved in the processes. In this study, we performed an integrated metagenomic and metatranscriptomic analysis on a chimney sample from Guaymas Basin to achieve a comprehensive study of each sulfur metabolic pathway and its hosting microorganisms and constructed the microbial sulfur cycle that occurs in the site. Our results clearly illustrated the stratified sulfur oxidation and sulfate reduction at the chimney wall. Besides, sulfur metabolizing is closely interacting with carbon cycles, especially the hydrocarbon degradation process in Guaymas Basin. This work supports that the internal sulfur cycling is intensive and the net sulfur budget is low in the hydrothermal ecosystem.